Metric pattern cutting for menswear - Aldrich, Winifred (Chichester, West Sussex : J. Wiley & Sons, 2011)
In this edition, the chapter on computer-aided design has been rewritten and expanded to reflect the growing importance of CAD in industry and as part of fashion and design courses. Other updates include new blocks for tailored shirts, details on fitting men's blocks for women's garments, and a revision of sizing and labelling.
Includes bibliographical references and index.
Keywords: Children's clothing -- Pattern design; Infants' clothing -- Pattern design; Garment cutting